2019
DOI: 10.3390/plants9010011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes Induced by Different Potassium Levels in Banana Roots

Abstract: Potassium plays an important role in enhancing plant resistance to biological and abiotic stresses and improving fruit quality. To study the effect of potassium nutrient levels on banana root growth and its regulation mechanism, four potassium concentrations were designed to treat banana roots from no potassium to high potassium. The results indicated that K2 (3 mmol/L K 2 SO 4 ) treatment was a relatively normal potassium concentration for the growth of banana root, and too high or too low potassium concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 115 publications
(128 reference statements)
0
17
0
Order By: Relevance
“…Auxin plays an important role in the growth and ripening of tomato fruit [ 56 ]. Another report suggested that potassium levels, which are important in fruit growth and quality, affect FKF1 expression in banana roots [ 31 ]. Therefore, the function of SlFKF1 may be related to auxin signaling and potassium nutrition in fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin plays an important role in the growth and ripening of tomato fruit [ 56 ]. Another report suggested that potassium levels, which are important in fruit growth and quality, affect FKF1 expression in banana roots [ 31 ]. Therefore, the function of SlFKF1 may be related to auxin signaling and potassium nutrition in fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FKF1-like sequences are conserved on the genomes of many plant species regardless of photoperiod responsiveness; short-day plants rice and soybean have phylogenetically FKF1-orthologous genes [ 22 , 28 ]. A few reports have suggested the possible functions of FKF1, such as stem and root growth and potassium response [ 29 , 30 , 31 ]. From these findings, it is expected that FKF1 plays various roles in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Nitrate transporter 1/peptide transporter ( NRT1/PTR ) genes regulated by external potassium has been reported for Arabidopsis [ 31 ], rice [ 34 ], wheat [ 67 ], banana [ 47 ], and pear [ 37 ]. Consistently, we identified several up-regulated GhNRT2.1s in the roots of SCRC22/CCRI41 ( Figure 6 a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, a number of authors have focused on low-K + stress using transcriptome, metabolome and proteomics analysis in model plants Arabidopsis and rice as well as other species [ 44 , 45 , 46 , 47 ]. However, there are no such reports on cotton yet to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao [ 7 ] screened different watermelon genotypes with low-K tolerance and found that short-term K-deficiency treatment had no negative effects on the plants. Sun [ 8 ] demonstrated that low-K treatment inhibited the growth of an apple rootstock ( Malus xiaojinensis ), allowing it to tolerate low K. Furthermore, low K had little effect on the length of banana primary roots but reduced root hairs [ 9 ]. Low-K stress reduced the number of lateral roots of tomatoes and increased root hairs in a K-efficient genotype of tomatoes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%